Sequence Variation and Expression Analysis of Seed Dormancy- and Germination-Associated ABA- and GA-Related Genes in Rice Cultivars - Liu, Fei; Zhang, Hangxiao; Wu, Gang; Sun, Jing; Hao, Lili; Ge, Xiaomeng; Yu, Jun; Wang, Weiwei (Frontiers in Plant Science, 2011)
Abscisic acid (ABA) and Gibberellic acid (GA) play key roles in regulating seed dormancy and germination. First, when examining germination of different rice cultivars, we found that their germination timing and dormancy status are rather distinct, coupled with different GA/ABA ratio. Second, we studied genomic sequences of ABA and GA dormancy- and germination-associated genes in rice and discovered single nucleotide polymorphisms (SNPs) and insertions/deletions (Indels) in both coding and regulatory sequences. We aligned all these variations to the genome assemblies of 9311 and PA64s and demonstrated their relevance to seed dormancy both quantitatively and qualitatively based on gene expression data. Third, we surveyed and compared differentially-expressed genes in dry seeds between 9311 and PA64s to show that these differentially-expressed genes may play roles in seed dormancy and germination.